Social Accounting: Assessing Corporate Commitment to Combatting Stunting in Indonesia through CSR Initiatives - Ifada Retno Ekaningrum; Agus Triyani; Nor Hadi; Siti Maisyaroh Bakti Pertiwi; M. Fatchurrohman; Setyo Mahanani (Universitas Pendidikan Ganesha, 2024)
This study evaluates the Corporate Social Responsibility (CSR) initiatives of companies in Indonesia's mining, basic materials, and cement industries, focusing on reducing stunting rates. Despite strong legislative and corporate mandates to address health issues, including stunting, a high prevalence continues, indicating that CSR efforts are neither sufficiently aligned nor effective. Using a qualitative descriptive approach and content analysis, this research analyzes 2023 annual and sustainability reports from 40 companies, uncovering a growing awareness and involvement in health sector CSR. However, efforts specifically targeting stunting are limited. The study identifies various CSR strategies and typologies, reflecting different levels of commitment and awareness aimed at improving initiative effectiveness. Despite these efforts, the study could not conclusively evaluate the impact of CSR on reducing stunting rates nor pinpoint factors behind its limitations. Further research is recommended to assess CSR effectiveness in stunting reduction and understand the obstacles to its success.